One-percent warrior [videorecording (Blu-Ray)] - Sakaguchi, Tak; Fukuyama, Kohei; Narumi, Kanon; Fukuda, Rumika; Yamaguchi, Yūdai, 1971-; Yamaguchi, Yūdai, 1971- (Well Go USA Entertainment, 2024)
A legendary, aging action film star is drawn into the real world of violence when feuding yakuza gangs infiltrate the set of his latest feature. Caught in the middle of a chaotic battle and increasing body count, will his martial arts training be enough to save him?